2022
DOI: 10.3390/molecules27072181
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Products of β-Aminopropioamidoximes Nitrobenzenesulfochlorination: Linear and Rearranged to Spiropyrazolinium Salts with Antidiabetic Activity

Abstract: Nitrobenzenesulfochlorination of β-aminopropioamidoximes leads to a set of products depending on the structure of the initial interacting substances and reaction conditions. Amidoximes, functionalized at the terminal C atom with six-membered N-heterocycles (piperidine, morpholine, thiomorpholine and phenylpiperazine), as a result of the spontaneous intramolecular heterocyclization of the intermediate reaction product of an SN2 substitution of a hydrogen atom in the oxime group of the amidoxime fragment by a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Thus, a number of the spiropyrazilinium tosylates studied in this article, as well as a number of previously reported nitrophenylsulfonates (Kayukova et al, 2022c), do not possess antitubercular activity, in contrast to the benzoates (Kayukova et al, 2021b), which exhibit average antitubercular activity. This allows us to conclude that arylsulfonate anions are not prospective for the synthesis of arylsulfonate derivatives of -aminopropioamidoximes with antitubercular activity.…”
Section: Intermolecular Interactionsmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, a number of the spiropyrazilinium tosylates studied in this article, as well as a number of previously reported nitrophenylsulfonates (Kayukova et al, 2022c), do not possess antitubercular activity, in contrast to the benzoates (Kayukova et al, 2021b), which exhibit average antitubercular activity. This allows us to conclude that arylsulfonate anions are not prospective for the synthesis of arylsulfonate derivatives of -aminopropioamidoximes with antitubercular activity.…”
Section: Intermolecular Interactionsmentioning
confidence: 49%
“…Finally, it was demonstrated using the example of piperidine spiropyrazolinium tosylate that the axial position of the nitrogen (N2) of the pyrazolinium heterocycle (ÁG = À144.3 kJ mol À1 ) with respect to the sixmembered ring is more preferable than the equatorial position with ÁG = À124.2 kJ mol À1 (Scheme 2). However, recently, for a series of solid 2-amino-1,5-diazospiro[4.5]dec-1-en-5-ium nitrobenzenesulfonates, the axial conformer was detected by means of XRD techniques (Kayukova et al, 2022c). Thus, interplay between the intermolecular interactions and the conformation of spiropyrazolines requires additional study.…”
Section: Introductionmentioning
confidence: 99%
“…However it is in what concerns medicinal chemistry that pyrazolines show their most representative properties including anticancer; , antimicrobial; antischistosomal; antitubercular; anti-inflammatory; , CB1 receptor antagonists (antiobesity); antidiabetic; anti-Parkinson; inhibitor of urease; immunosuppressive; antidepressant; CNS uses; 18 F labeled radiotracers; and chemical libraries …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the authors reported the results of the in vitro screening of the library of nitrobenzenesulfochlorination products for anti-diabetic activity. Two distinct compounds, obtained in the p-nitrobenzenesulfochlorination of β-(thiomorpholin-1-yl)and β-(benzimidazol-1-yl)propioamidoximes showed high α-glucosidase activity superior to the activity of the acarbose standard [5]. J.-C. Rodríguez-Ubis and coworkers reported an orthogonal synthetic approach to non-symmetrical bisazolyl 2,4,6-trisubstituted pyridines, important ligands in a variety of transition and lanthanide ions complexes, starting from the readily available 4-bromo-2,6-difluoropyridine.…”
mentioning
confidence: 98%
“…By using different bases, reaction media, and temperatures, regioselective alkylation was achieved, and the established conditions were applied to the synthesis of novel pyrazolo[1,5a] [1,4]diazepin-4-ones via the ring-opening of the oxirane with amines and a direct cyclisation sequence. They further applied this synthetic strategy to investigate the reactivity of ethyl 1H-indole-2-carboxylate and ethyl benzo[d]imidazole-2-carboxylate scaffolds, which led to the formation of additional fused tetrahydro [1,4]diazepino [1,2-a]indol-1one and tetrahydro-1H-benzo [4,5]imidazo [1,2-a] [1,4]diazepin-1-one derivatives [1]. Polyfunctionalized pyrazoles, of general interest in medicine and material sciences, were the subject studied by M. Jasi ński and coworkers, who described a solvent-free two-step mechanochemical synthesis of trifluoromethylated and non-fluorinated polysubstituted pyrazoles in moderate-to-high regioselectivity and fair yields, starting from simple substrates, chalcones, and hydrazonoyl halides.…”
mentioning
confidence: 99%